Portfolio to go : 1000+ reflective writing prompts and provocations for clinical learners - Peterkin, Allan (University of Toronto Press, 2016)
In Portfolio To Go, Allan D. Peterkin insists that reflective capacity, critical thinking, creative expression, and narrative competence are attributes that should be developed in every health professional.